Development of pVCR94ΔX from Vibrio cholerae, a prototype for studying multidrug resistant IncA/C conjugative plasmids - Carraro, Nicolas; Sauvé, Maxime; Matteau, Dominick; Lauzon, Guillaume; Rodrigue, Sébastien; Burrus, Vincent (Frontiers in Microbiology, 2014)
Antibiotic resistance has grown steadily in Vibrio cholerae over the last few decades to become a major threat in countries affected by cholera. Multi-drug resistance (MDR) spreads among clinical and environmental V. cholerae strains by lateral gene transfer often mediated by integrative and conjugative elements (ICEs) of the SXT/R391 family. However, in a few reported but seemingly isolated cases, MDR in V. cholerae was shown to be associated with other self-transmissible genetic elements such as conjugative plasmids. IncA/C conjugative plasmids are often found associated with MDR in isolates of Enterobacteriaceae. To date, IncA/C plasmids have not been commonly found in V. cholerae or other species of Vibrio. Here we present a detailed analysis of pVCR94ΔX derived from pVCR94, a novel IncA/C conjugative plasmid identified in a V. cholerae clinical strain isolated during the 1994 Rwandan cholera outbreak. pVCR94 was found to confer resistance to sulfamethoxazole, trimethoprim, ampicillin, streptomycin, tetracycline, and chloramphenicol and to transfer at very high frequency. Sequence analysis revealed its mosaic nature as well as high similarity of the core genes responsible for transfer and maintenance with other IncA/C plasmids and ICEs of the SXT/R391 family. Although IncA/C plasmids are considered a major threat in antibiotics resistance, their basic biology has received little attention, mostly because of the difficulty to genetically manipulate these MDR conferring elements. Therefore, we developed a convenient derivative from pVCR94, pVCR94ΔX, a 120.5-kb conjugative plasmid which only codes for sulfamethoxazole resistance. Using pVCR94ΔX, we identified the origin of transfer (oriT) and discovered an essential gene for transfer, both located within the shared backbone, allowing for an annotation update of all IncA/C plasmids. pVCR94ΔX may be a useful model that will provide new insights in the basic biology of IncA/C conjugative plasmids.